Survival impact of bowel resection at the time of interval cytoreductive surgery for advanced ovarian cancer - Blair McNamara; Rosa Guerra; Jennifer Qin; Amaranta D. Craig; Lee-may Chen; Madhulika G. Varma; Jocelyn S. Chapman (Elsevier, 2021)
Objectives: To evaluate the impact of bowel resection at the time of interval cytoreductive surgery on survival. Methods: We identified patients with advanced ovarian cancer who underwent neoadjuvant chemotherapy and interval cytoreductive surgery between 2008 and 2018 from a single-institution tumor registry. Kaplan-Meier survival analysis and Cox proportional hazards models were performed comparing patients who underwent bowel resection to those who did not. Results: Of 158 patients, 43 (27%) underwent bowel resection. Rates of optimal (95%) and sub-optimal (5%) resection did not differ with bowel resection. Patients that required bowel resection had worse three-year survival (43% vs. 63%), even after adjusting for confounding variables of age, stage, number of neoadjuvant cycles, R0 resection, and ASA score (HR 2.27, p < 0.01). Adjusted progression-free survival did not differ between groups (HR 0.92, p = 0.72). Patients who underwent bowel resection were more likely to require blood transfusion (p < 0.01), and have a longer hospital stay (5 days vs 7.5 days, p < 0.01). Conclusions: Bowel resection at the time of interval cytoreduction confers a greater than 2-fold increased risk of mortality and does not impact progression-free survival. Long-term sequelae of the peri-operative morbidity of bowel resection may contribute to increased mortality, and bowel resection may be a surrogate for disease biology with poor prognosis.